Detección faríngea de chlamydia trachomatis asociada a sospecha de abuso sexual - Kiguen, Ana Ximena; Ochonga, Graciela; Venezuela, Raul Fernando; Monetti, Marina; Frutos, María Celia; Mosmann, Jessica; Cuffini, Cecilia (Asociación Argentina de Microbiología, 2022)
1 p.